2004
DOI: 10.1590/s0100-879x2004001100019
|View full text |Cite
|
Sign up to set email alerts
|

Normative data for the Brazilian population in the Boston Diagnostic Aphasia Examination: influence of schooling

Abstract: In Neurolinguistics, the use of diagnostic tests developed in other countries can create difficulties in the interpretation of results due to cultural, demographic and linguistic differences. In a country such as Brazil, with great social contrasts, schooling exerts a powerful influence on the abilities of normal individuals. The objective of the present study was to identify the influence of schooling on the performance of normal Brazilian individuals in the Boston Diagnostic Aphasia Examination (BDAE), in or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
44
2
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 5 publications
9
44
2
7
Order By: Relevance
“…Therefore, individuals with five years of schooling or more performed better ( Table 1). Our study identified differences in these tasks according to schooling level ( Table 1), and our findings are in agreement with those of Radanovic et al 8 The study by the latter authors involved applying the Boston test, and it also found differences according to schooling, in relation to the tasks of naming by visual comparison (written task based on pictures), reading of paragraphs and sentences and firstlevel dictation (word dictation). Their results clearly showed that exposure to formal schooling promotes development in these skills.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Therefore, individuals with five years of schooling or more performed better ( Table 1). Our study identified differences in these tasks according to schooling level ( Table 1), and our findings are in agreement with those of Radanovic et al 8 The study by the latter authors involved applying the Boston test, and it also found differences according to schooling, in relation to the tasks of naming by visual comparison (written task based on pictures), reading of paragraphs and sentences and firstlevel dictation (word dictation). Their results clearly showed that exposure to formal schooling promotes development in these skills.…”
Section: Discussionsupporting
confidence: 92%
“…18,22,23 One hypothesis for this could be that schooling facilitates organization of categories and semantic subgroups. 18 In our study, the mean score in the lexical availability task among the normal healthy subjects was approximately 19 ( 8 in studies that did not include illiterate subjects or those with less than four years of formal education.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Aphasia is a disturbance in the processing of language secondary to brain lesion (2) . Language is strongly influenced by gender, age and schooling besides other sociocultural characteristics (3,4) . In neurolinguistics, the use of tests developed in other countries for diagnosing aphasia can hamper the interpretation of results due to language, demographic and cultural differences.…”
Section: Introductionmentioning
confidence: 99%
“…As science progresses, models are being reviewed and some skills (such as auditory verbal memory and working memory) are being directly linked to language processing. As ethics and client centered perspectives postulate, clinical practice should follow scientific progress [14,15].…”
Section: Discussionmentioning
confidence: 99%